Gay dan Lesbian Indonesia serta Gagasan Nasionalisme - Tom Boellstorff (Antropologi Indonesia, 2006)
This essay argues for paying attention to the life-worlds of gay and lesbian Indonesians. These Indonesians' lives provide valuable clues to how being 'Indonesian' gets defined and to the workings of nation-states more generally. In particularly, the lives of gay and lesbian Indonesians help to demonstrate how heteronormativity the assumption that heterosexuality is the only normal or proper sexuality plays a fundamental role in forming nation-states as "imagined communities." Restricting the family model to the heterosexual couple has been a key means by which the idea of the Indonesian nation (and other nations) has been promulgated and sustained. Thus, rather than see the exclusion of homosexuality as a latter-day response to an encroaching global gay and lesbian movement, this exclusion is most accurately understood as a point of departure by which the idea of 'Indonesia' comes to exist in the first place. Keywords: Gay, lesbian, homosexuality, Indonesia, nation.